To the Substantiation of the Joint Use of Vitamin D and the Rest of the 12 Vitamins Necessary for the Creation and Realization of the Vital Functions of its Hormone-Active Form (The Vitamin D + 12 Vitamins Approach) - Spirichev, V.B. (Journal of Nutritional Therapeutics, 2013)
The realization of the multiple vital functions of vitamin D in a human organism closely depends on the sufficient provision of the rest of the vitamins necessary for the creation of the hormone-active form of vitamin D, as well as on the normal realization of the vital biochemical and physiological processes it controls. The above report substantiates the expediency of the combined application of vitamin D and a complex including the rest of the 12 vitamins both for the medical treatment and prevention of diseases (the D + 12 vitamins approach).